Let's go through the equation step by step, starting with the original equation:
\[2(-10p - 20) + 16p = 5p - 4.\]
Step 1: Apply the Distributive Property
Distributing on the left side:
\[2(-10p) + 2(-20) + 16p = 5p - 4.\]
This simplifies to:
\[-20p - 40 + 16p = 5p - 4.\]
Step 2: Combine Like Terms on the Left Side
Combine \(-20p\) and \(16p\):
\[-20p + 16p - 40 = 5p - 4.\]
This becomes:
\[-4p - 40 = 5p - 4.\]
Step 3: Isolate the Variable
Next, we want to isolate \(p\). Let's add \(4p\) to both sides:
\[-40 = 5p + 4p - 4,\]
which simplifies to:
\[-40 = 9p - 4.\]
Step 4: Add 4 to Both Sides
Now, we add 4 to both sides:
\[-40 + 4 = 9p - 4 + 4,\]
which gives:
\[-36 = 9p.\]
Step 5: Divide by 9
To solve for \(p\), divide both sides by 9:
\[\frac{-36}{9} = p,\]
which simplifies to:
\[p = -4.\]
Conclusion
The solution to the equation is:
\[p = -4.\]